Cinacalcet versus standard treatment for chronic kidney disease: a systematic review and meta-analysis. (2nd July 2016) - Sekercioglu, Nigar; Busse, Jason W.; Sekercioglu, M. Fatih; Agarwal, Arnav; Shaikh, Shaun; Lopes, Luciane Cruz; Mustafa, Reem A.; Guyatt, Gordon H.; Thabane, Lehana
Abstract: Background: Chronic kidney disease-mineral and bone disorders (CKD-MBD) have been associated with poor health outcomes, including diminished quality and length of life. Standard management for CKD-MBD includes phosphate restricted diet, vitamin D and phosphate binders. Persistently elevated parathyroid hormone levels may require the addition of cinacalcet hydrochloride (cinacalcet), which sensitizes calcium receptors in the parathyroid gland. Purpose: The objective of this systematic review is to compare, in patients with CKD-MBD the effect of cinacalcet versus standard treatment on patient-important outcomes, including parathyroidectomy, fractures, hospitalizations due to cardiovascular events, cardiovascular mortality, all-cause mortality, and intermediate outcomes, in particular Kidney Disease Outcome Quality Initiative targets. Methods: Data sources included MEDLINE, EMBASE, the Cochrane Register of Controlled Trials and Web of Science from 1996 to June 2015. Teams of two reviewers, independently and in duplicate, screened titles and abstracts and potentially eligible full text reports to determine eligibility, and subsequently abstracted data and assessed risk of bias in eligible trials. We calculated the effect estimates (risk ratios or mean differences) and 95% confidence intervals, as well as statistical measures of variability in results across studies using random effect models. We used the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach to rate quality of evidence about estimates of effect on an outcome-by-outcome basis for all outcomes. We presented our results with a GRADE summary table. Results: Twenty-four trials including 8311 CKD patients proved eligible. The results left considerable uncertainty regarding the impact of cinacalcet on reducing fractures (relative risk [RR] 0.59, 95% confidence interval [CI] 0.13–2.60; heterogeneity: p =  0.03, I 2 = 78%; very low quality evidence), and indicated that cinacalcet did not reduce hospitalizations due to cardiovascular events (RR 0.93, 95% CI 0.85–1.02, moderate quality of evidence), cardiovascular mortality (RR 0.95, 95% CI 0.84–1.07; heterogeneity p=  0.61, high quality evidence) or all-cause mortality (RR 0.96, 95% CI 0.89–1.04; heterogeneity: p=  0.98, I 2 = 0%; moderate quality evidence). Cinacalcet reduced the need for parathyroidectomy (RR 0.30, 95% CI 0.22–0.42; heterogeneity: p=  0.70, I 2 = 0%; absolute effect 55 fewer per 1000 [95% CI 61 fewer to 45 fewer], high quality of evidence). The most common adverse event associated with cinacalcet therapy was gastrointestinal side effects. Cinacalcet increased nausea (RR 2.16, 95% CI 1.46–3.21, absolute effect 158 more per 1000 [95% CI 82 more to 302 more]) and vomiting (RR 2.15, 95% CI 1.66–2.80, absolute effect 63 more per 1000 [95% CI 109 more to 171 more]). Cinacalcet treatment increased the rate of hypocalcemia (RR 6.0, 95% CI 3.65–9.87; heterogeneity: p=  0.71, I 2 = 0%, absolute effect 20 more per 1000 [95% CI 11 more to 36 more], high quality of evidence). Conclusions: In the hands of clinicians participating in these studies, cinacalcet decreased the rate of parathyroidectomy but had no influence on mortality. Patients and clinicians can trade of the benefit of fewer parathyroidectomies against the adverse effects.